Establishment of an a priori protocol for the implementation and interpretation of an in‐vitro testing battery for the assessment of developmental neurotoxicity. Issue 10 (23rd October 2020) - Masjosthusmann, Stefan; Blum, Jonathan; Bartmann, Kristina; Dolde, Xenia; Holzer, Anna‐Katharina; Stürzl, Lynn‐Christin; Keßel, Eike Hagen; Förster, Nils; Dönmez, Arif; Klose, Jördis; Pahl, Melanie; Waldmann, Tanja; et al.
Abstract : In this project we set up a human cell‐based DNT in vitro testing strategy that is based on test methods with high readiness and data generated therefrom. The methods underwent afit‐for‐purpose evaluation that considered four key elements: 1. The test system, 2. the exposure scheme, 3. the assay and analytical endpoint(s) and 4. the classification model. This testing battery was challenged with 119 chemicals for which rich toxicological information was available (for some of them also on their DNT hazard). Testing was performed in 5 test systems measuring 10 DNT‐specific endpoints and additional 9 viability/cytotoxicity‐related parameters. For approximately half of the compounds, additional and complementary data from DNT  in vitro tests was added by the US‐EPA. This extended battery was also evaluated. Testing results revealed that the test methods of this current DNT in vitro battery are reliable and reproducible. The endpoints had to a large extent low redundancy. Battery performance, as assessed with compounds well‐characterized for DNT hazard had a sensitivity of 82.7% and a specificity of 88.2%. Gap analyses suggested that radial, astro‐ and microglia as well as myelination endpoints may be added to the battery. Two case studies, one for screening and prioritization of 14 flame retardants, and one on hazard characterization of 2 pesticides, were presented. Hypothetical AOPs were developed based on the latter case study.In conclusion, the DNT testing strategy explored here is a very promising first approach for DNT hazard identification and characterization. The performance is encouraging and may be improved by inclusion of further tests. Some uncertainties in DNT in vitro battery testing outcomes could be reduced by incorporating test data and modelling approaches related to in vitro and  in vivo toxicokinetics of test compounds.